The Polemic of Nasab and the Degradation of Habib's Religious Authority in Contemporary Indonesia - Ahmadi, Sambirang; Fahrurrozi, Fahrurrozi; Wahid, Abdul; Aziz, Amir; Sulaiman, Adibah (Prodi Aqidah dan Filsafat Islam, Fakultas Ushuluddin, Universitas Islam Negeri Sunan Kudus, 2026)
This article examines the contemporary polemic surrounding the genealogy (nasab) of habaib in Indonesia and its implications for the transformation of religious authority in the digital age. The controversy was triggered by Kiai Imaduddin’s study, which questioned the genealogical connection of habaib to the Prophet Muhammad, thereby challenging their status as zurriyat. As this issue circulated widely through digital media, it generated intense and contested public debates among Indonesian Muslims. Employing a netnographic approach, this study traces the dynamics of the genealogy polemic through online interactions across social media platforms, digital forums, and online sites. Data were collected through virtual participant observation, systematic documentation of online discussions, and qualitative content analysis of both supportive and opposing narratives. The findings indicate that, first, digital spaces have become primary arenas for negotiating and contesting religious authority and legitimacy; second, new media are strategically utilized to deconstruct the symbolic authority of habaib through discourses questioning the continuity of their lineage with the Prophet Muhammad; and third, the genealogy polemic is closely linked to political polarization since the Jakarta gubernatorial election and the 2014 and 2019 presidential elections, which intensified ideological fragmentation between segments of Nahdlatul Ulama clerics and habaib in their views on the relationship between Islam and democracy. This article concludes that the genealogy polemic is not merely a genealogical dispute but reflects a broader process of reconfiguration of Islamic authority under conditions of digital mediatization and political fragmentation. By demonstrating how online platforms reshape religious legitimacy and public trust, this study contributes to wider debates on the transformation of authority and political polarization in contemporary digital Muslim societies.